PUBLIC ENVIRONMENTAL MONITORING OF THE STATE OF SNOWPACK IN NORILSK - N. V. Karmanovskaya; O. V. Nosova; A. V. Kaverzin (Academic Scientific Journal of Chemistry, 2021)
It is considered that Norilsk ranks second in terms of atmospheric contamination. Industrial enterprises annually emit large amounts of sulphur dioxide, phenols, and heavy metal particles. The city is located within the Far North and is distinguished by the harsh climate of the subarctic type. The snow cover can lie from 244 to 277 days. Snow is a good sorbent; therefore, the snow cover accumulates solid and gaseous pollutants that enter it from the atmosphere with precipitation or are absorbed from it. The purpose of this study was to analyse the snow cover in the Norilsk industrial region and assess the state of atmospheric air in the winter. To achieve this goal, it is necessary to solve the following tasks: conduct a literature review on a given topic; take samples of snow in various industrial districts of Norilsk; study the dependence of the qualitative characteristics of snow on the sampling site; draw conclusions on the quality of snowpack in different areas of the industrial districts of Norilsk. In the course of the study, the following methods were used: organoleptic, visual, methods for determining water transparency, titrimetric analysis, etc. Heavy metal ions and sulphate ions were not detected in the thawed snow, so no industrial gas pollution was noted in the residential area. Most of the particulate contamination was caused by slagging of roads to improve vehicle traction